2017
DOI: 10.21826/2446-8231201772306
|View full text |Cite
|
Sign up to set email alerts
|

First Insights Into Micromorphology of Needle Epicuticular Waxes of South-Eastern European Pinus Nigra J. F. Arnold Populations

Abstract: This is the fi rst insight into the fi ne structure of the epicuticular wax crystalloids found on the adaxial surfaces of needles from three Pinus nigra subspecies (ssp. nigra, ssp. banatica (Borbás) Novák, and ssp. pallasiana (Lamb.) Holmboe) growing wild in the southeastern Europe. In general, the main wax crystalloids in P. nigra taxa were tubules, fairly dense, with reticular aspect and restricted to suprastomatal chambers. The P. nigra needles have amorphous wax-smooth layers, granules, alone tubes lying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…In this sense, Boddi et al [ 58 ] described teeth or spine-like structures in transverse sections as more elongated cells with cytoplasmic content differing from the adjacent epidermic cells for thicker walls; however, the relevance of these structures is unknown. A scanning electron micrograph revealed stomata arranged in parallel and as uniseriate bands, which is in accordance with the work described for P. nigra by Mitic et al [ 59 ]. Similar to that observed in P. halepensis , [ 58 ] large and ovoidal stomata were detected in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this sense, Boddi et al [ 58 ] described teeth or spine-like structures in transverse sections as more elongated cells with cytoplasmic content differing from the adjacent epidermic cells for thicker walls; however, the relevance of these structures is unknown. A scanning electron micrograph revealed stomata arranged in parallel and as uniseriate bands, which is in accordance with the work described for P. nigra by Mitic et al [ 59 ]. Similar to that observed in P. halepensis , [ 58 ] large and ovoidal stomata were detected in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The teeth structures on the needle surface were morphologically similar to those found in primary needles of P. halepensis and P. nigra [ 58 , 59 ]. In this sense, Boddi et al [ 58 ] described teeth or spine-like structures in transverse sections as more elongated cells with cytoplasmic content differing from the adjacent epidermic cells for thicker walls; however, the relevance of these structures is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Such a restriction of the crystalloids to the needle surface with stomatal complexes suggested that the structural wax originates associated with the stomatal complex. In accordance, many studies have shown that wax tubules on needles are not distributed evenly in Pinales, considering their tendency to be concentrated near stomata and between them in the stomatal rows (Crossley & Fowler 1986;Kim et al 2011;Ivănescu et al 2008;Mitić et al 2017). Epicuticular wax tubules on A. alba needles are deposited only on the abaxial surface where stomatal complexes occur (Bačić & Popović 1998), just as observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance, our study showed increasing degradation of tubules on Abies needles with the needle aging. These changes in the appearance of structural waxes are part of the natural aging process, and gradually all structural wax degrades to granules or amorphous crusts (Mitić et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation